Anatomical Study of the Duodenojejunal Uncinate Process Vein: A Key Landmark for Mesopancreatoduodenal Resection During Pancreaticoduodenectomy. Issue 2 (12th October 2021) - Honjo, Masahiko; Tohyama, Taiji; Ogawa, Kohei; Tamura, Kei; Sakamoto, Katsunori; Takai, Akihiro; Watanabe, Jota; Ohtani, Hiromi; Takada, Yasutsugu
Abstract: Background: The mesopancreas or mesopancreatoduodenum is an important anatomical concept during pancreaticoduodenectomy (PD) in patients with periampullary carcinoma. This study investigated whether the duodenojejunal uncinate process vein (DJUV), which is defined as the vein draining from the upper jejunum to the superior mesenteric vein adjacent to the uncinate process, is a useful anatomical landmark for the caudal border of mesopancreatoduodenum resection during PD. Methods: This study enrolled 100 adult patients with hepatobiliary pancreatic disease who underwent preoperative multidetector‐computed tomography (CT). The anatomy of the key blood vessels involved during PD, and the relationship between these vessels and the DJUV, were analyzed by preoperative CT. Results: The first jejunal vein was the DJUV in 85 cases, whereas the second jejunal vein was the DJUV in 15 cases. Furthermore, the DJUV was classified into two subtypes depending on its positional relationship with the superior mesenteric artery (SMA). The inferior pancreaticoduodenal artery and vein were located on the cranial side of the DJUV in all cases. The distance between the middle colonic artery, used as a guide for regional lymph nodes, and the point where the DJUV intersected the SMA was within 10 mm in 80% of cases. These results imply that using the DJUV as a landmark for the caudal border of the mesopancreatoduodenum provides a safe approach and enables sufficient dissection of regional lymph nodes and tissues around the SMA. Conclusion: The DJUV may be a useful anatomical landmark for the caudal border of the mesopancreatoduodenum resection during PD. Abstract : The mesopancreas or mesopancreatoduodenum is an important anatomical concept during pancreaticoduodenectomy (PD) in patients with periampullary carcinoma. This study investigated whether the duodenojejunal uncinate process vein (DJUV), which is defined as the vein draining from the upper jejunum to the superior mesenteric vein adjacent to the uncinate process, is a useful anatomical landmark for the caudal border of mesopancreatoduodenum resection during PD.